Limbic and whole-brain functional connectivity in non-substance abusers with human immunodeficiency virus (HIV) - Stuart D. Washington; Anisa Thomas; Kehinde Omisore; Cedric Cole; Tomilowo Abijo; Ashley VanMeter; Marjorie C. Gondré-Lewis (Journal of NeuroVirology, 2026)

Fistulous withers causing spinal epidural abscess in a Thoroughbred mare - Serena Ceriotti; Stuart Clark-Price; Robert Cole; Alana Kramer; Maninder Sandey; Mariano Mora (Journal of Equine Veterinary Science, 2025)

Deep learning-based plastic classification using spectroscopic data - Aru Ranjan Singh; Edward Ren Kai Neo; Car Man Lai; Sumit Hazra; Stuart Coles; Ton Peijs; Kurt Debattista (Journal of Cleaner Production, 2025)

Closed-loop recycling of reclaimed short carbon fibre reinforced polyamide composites - Adrian Lopera-Valle; Peter Wilson; Stuart R. Coles; Kerry Kirwan (Journal of Cleaner Production, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

First cycle or polycyclic? Combining apatite and zircon detrital U-Pb geochronology and geochemistry to assess sediment recycling and effects of weathering - Emily S. Finzel; Stuart N. Thomson; David M. Pearson; L．Kenneth Horkley; Kacey Garber; Cole Gardner (Earth and Planetary Science Letters, 2025)

Simulation of bench-scale CO2 injection using a coupled continuum-discrete approach - Nicholas A. Ashmore; Magdalena M. Krol; Stuart M.V. Gilfillan; Cole J.C. Van De Ven; Kevin G. Mumford; Ian L. Molnar (Science of The Total Environment, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

The impact of a low traffic neighbourhood intervention on urban noise measured with low-cost sensors in Oxford, UK - Felix C.P. Leach; Jingyuan Yang; Varun Shankar; Stuart Cole; Katie Parnell; Mani Entezami; Suzanne E. Bartington (Transportation Research Part D: Transport and Environment, 2024)

Inter-laboratory re-determination of the atmospheric 22Ne/20Ne - Domokos Györe; Hirochika Sumino; Inseok Yang; László Palcsu; Elemér László; M. Cole Bishop; Sujoy Mukhopadhyay; Finlay M. Stuart (Chemical Geology, 2024)

Are UK E-waste recycling facilities a source of environmental contamination and occupational exposure to brominated flame retardants? - Yulong Ma; Ester Konecna; Reginald Cline-Cole; Stuart Harrad; Mohamed Abou-Elwafa Abdallah (Science of The Total Environment, 2023)

Cross-modal generative models for multi-modal plastic sorting - Edward R.K. Neo; Jonathan S.C. Low; Vannessa Goodship; Stuart R. Coles; Kurt Debattista (Journal of Cleaner Production, 2023)

The impact of COVID-19 public health restrictions on particulate matter pollution measured by a validated low-cost sensor network in Oxford, UK - Tony Bush; Suzanne Bartington; Francis D. Pope; Ajit Singh; G. Neil Thomas; Brian Stacey; George Economides; Ruth Anderson; Stuart Cole; Pedro Abreu; Felix C.P. Leach (Building and Environment, 2023)

The offshore renewables industry may be better served by new bespoke design guidelines than by automatic adoption of recommended practices developed for oil and gas infrastructure: A recommendation illustrated by subsea cable design - Terry Griffiths; Scott Draper; Liang Cheng; Hongwei An; Marie-Lise Schläppy; Antonino Fogliani; David White; Stuart Noble; Daniel Coles; Fraser Johnson; Bryan Thurstan; Yunfei Teng (Frontiers in Marine Science, 2023)
Introduction There is an emerging need for the offshore renewable industry to have their own bespoke design guidelines because the associated projects and offshore facilities differ in fundamental ways to oil and gas facilities. Offshore renewable energy (ORE) facilities have already surpassed the numbers of installed facilities in the oil and gas industry by an order of magnitude and demand is forecast to continue growing exponentially. In addition ORE facilities often have different response characteristics and limit states or failure modes as well as profoundly different risk and consequence profiles given they are generally uncrewed and do not contain explosive hydrocarbon fluids which might be released into the environment. Therefore, the purpose of this paper is to advocate for licensing bodies and regulators (such as the various national PEL 114 committees) to challenge the process of automatic adoption of oil and gas design processes, while pushing for offshore renewables to be treated differently, when appropriate, with more relevant and applicable guidance. Methods To support this argument we present new bespoke design guidance developed for subsea cables based on specific modes of cable behaviour, which often differ from pipelines. We also show worked examples from recent project experience. The results from on-bottom stability analyses of a set of cables are compared between conventional oil and gas guidance following DNV-RP-F109 versus the stability using cable-optimised approaches. Results The outcomes from the ‘conventional’ oil and gas results are not simply biased compared to cable-optimised design methods, with a trend of being either conservative or unconservative. Instead, the results of the two methods are very poorly correlated. This shows that the oil and gas approach isn't simply biased when applied to cables, but is instead unreliable because it doesn't capture the underlying failure conditions. These analytical comparisons are supported by field observation - the ocean doesn't lie, and makes short work of any anthropogenic structures which are designed with inadequate appreciation of the real world conditions. Discussion To support the rapid growth of ORE, we should therefore actively pursue opportunities to rewrite the design rules and standards, so that they better support the specific requirements of ORE infrastructure, rather than legacy oil and gas structures. With more appropriate design practices, we can accelerate the roll out of ORE to meet net zero, and mitigate the climate crisis.

Temporal trends in concentrations of brominated flame retardants in UK foodstuffs suggest active impacts of global phase-out of PBDEs and HBCDD - Yulong Ma; William A. Stubbings; Mohamed Abou-Elwafa Abdallah; Reginald Cline-Cole; Stuart Harrad (Science of The Total Environment, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Life cycle assessment of lignocellulosic biomass pretreatment methods in biofuel production - Aashish Prasad; Maria Sotenko; Thomas Blenkinsopp; Stuart R. Coles (The International Journal of Life Cycle Assessment, 2016)

Workshop on life cycle sustainability assessment: the state of the art and research needs—November 26, 2012, Copenhagen, Denmark - Marco Cinelli; Stuart R. Coles; Andreas Jørgensen; Alessandra Zamagni; Chalaka Fernando; Kerry Kirwan (The International Journal of Life Cycle Assessment, 2013)

Conserved anchorless surface proteins as group A streptococcal vaccine candidates - Anna Henningham; Emiliano Chiarot; Christine M. Gillen; Jason N. Cole; Manfred Rohde; Marcus Fulde; Vidiya Ramachandran; Amanda J. Cork; Jon Hartas; Graham Magor; Steven P. Djordjevic; Stuart J. Cordwell; et al. (Journal of Molecular Medicine, 2012)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Chlorophyll fluorescence measures of seagrasses Halophila ovalis and Zostera capricorni reveal differences in response to experimental shading - Juanita S. Bité; Stuart J. Campbell; Len. J. McKenzie; Robert G. Coles (Marine Biology, 2007)

Seasonal effects of extreme surges - Stuart Coles; Jonathan Tawn (Stochastic Environmental Research and Risk Assessment, 2005)

The EPAS1 gene influences the aerobic–anaerobic contribution in elite endurance athletes - Jennifer Henderson; Jason M. Withford-Cave; David L. Duffy; Stuart J. Cole; Nicole A. Sawyer; Jason P. Gulbin; Allan Hahn; Ronald J. Trent; Bing Yu (Human Genetics, 2005)

Identification, expression analysis, and mapping of B3galt6, a putative galactosyl transferase gene with similarity to Drosophila brainiac - Susan E. Cole; Meredith S. Mao; Stuart H. Johnston; Thomas F. Vogt (Mammalian Genome, 2001)